2016
DOI: 10.1016/j.bcp.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Serum- and glucocorticoid-inducible kinase SGK2 regulates human organic anion transporters 4 via ubiquitin ligase Nedd4-2

Abstract: Human organic anion transporter 4 (hOAT4) belongs to a family of organic anion transporters that play critical roles in the body disposition of clinically important drugs, including anti-viral therapeutics, anti-cancer drugs, antibiotics, antihypertensives, and anti-inflammatories. hOAT4 is abundantly expressed in the kidney and placenta. In the current study, we examined the regulation of hOAT4 by serum- and glucocorticoid-inducible kinase 2 (sgk2) in the kidney COS-7 cells. We showed that sgk2 stimulated hOA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…We showed that in contrast to the inhibitory effect of PKC, sgk2 stimulated OAT1 and OAT4 transport activity. Such stimulation mainly resulted from an increased cell surface expression of the transporter, kinetically revealed as an increased maximal transport velocity Vmax without significant change in substrate‐binding affinity Km . We further showed that the regulation of OAT4 activity by sgk2 was mediated by ubiquitin ligase Nedd4‐2.…”
Section: Regulation Of Oat By Ubiquitinationmentioning
confidence: 74%
See 2 more Smart Citations
“…We showed that in contrast to the inhibitory effect of PKC, sgk2 stimulated OAT1 and OAT4 transport activity. Such stimulation mainly resulted from an increased cell surface expression of the transporter, kinetically revealed as an increased maximal transport velocity Vmax without significant change in substrate‐binding affinity Km . We further showed that the regulation of OAT4 activity by sgk2 was mediated by ubiquitin ligase Nedd4‐2.…”
Section: Regulation Of Oat By Ubiquitinationmentioning
confidence: 74%
“…In addition to PKC, we recently demonstrated that the serum‐ and glucocorticoid‐inducible kinase 2 (sgk2) also regulates OAT activity via Nedd4‐2 . The sgk family of protein kinases has three isoforms: sgk1, sgk2, and sgk3 that are involved in controlling diverse cellular processes including sodium Na + homeostasis, osmoregulation, cell survival, and cell proliferation .…”
Section: Regulation Of Oat By Ubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed procedure has been reported previously (Wang et al, ; Xu et al, ). The cells were lysed with lysis buffer and then precleared with protein G‐agarose beads (Pierce, Rockford, IL) at 4°C for 2 h to reduce nonspecific binding.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, sgk2 is insensitive to such regulation. Our laboratory recently demonstrated that sgk2 plays a significant role in the regulation of OATs (Wang, Xu, Toh, Pao, & You, ; Xu et al, ). However, the role of sgk1 in OAT function has not been explored.…”
Section: Introductionmentioning
confidence: 99%